Engaging in the leadership process : identity, capacity, and efficacy for college students - Guthrie, Kathy L.; Beatty, Cameron C.; Wiborg, Erica R. (Contemporary perspectives on leadership learning., 2021)
"This book introduces readers to process-based understandings of leadership, providing language and tools for engaging in the leadership process for all involved. This practical book was designed for college student leaders and educators or professionals who work with student leaders on college campuses. However, it is also accessible for high school students and graduate students to reflect on their identity, capacity, and efficacy as leaders. Based on their experiences as leadership educators, the authors offer grounding concepts of leadership and examples illustrating the complexity of culturally relevant leadership learning. Identity (who you are), capacity (your ability), and efficacy (what you do) are important for students to explore leadership development. These three concepts are core to this book, filling a gap in college student development literature by defining, illustrating, and questioning how they matter to leadership learning. Framing leadership as a journey, this resource offers key learning opportunities for students to engage with others through a range of contexts. Each chapter is organized with various features, engaging readers to get the most out of this book. Features include "call-in boxes" to prepare for learning and "pause for considerations" to apply to personal experiences. Chapters conclude with personal reflection questions, discussion questions, and activities to take leadership learning further. The features are designed to be accessible for utilization in classes, organizations, community work, groups, and individual reflection opportunities"--